Pola Komunikasi Interpersonal Pada Perkawinan Campuran Masyarakat Suku Sasak dengan Warga Negara Asing di Pulau Lombok - Novita Maulida (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2023)
This research is to emphasize the communication in intermarriage between Sasak tribe and foreigner in Lombok Island. This research uses descriptive qualitative as an approach to be used a phenomenology tradition which focuses on someone’s experience, so that the theory of communication in intercultural can be understood by the people easily. The object of this research is three couples of interviewees who had intermarriage in Lombok Island with their various and background. It is intended to do the comparisonof searching and revealing the experience for each individual. Then it will get something that can be a contribution to the theme, intercultural communication in the context of intermarriage. To face the problem of communication in intercultural in that context, stereo type can affect the appraisal of a big family to someone who will be his or her soul mate. The intermarriage couples need extraordinary commitment, so that every single mistake can be solved easily. Including when each individual does the adaptation, they hope that the marriage can happen and get an easiest way from their big family. The second problem is personal background or individual perpetrators of intermarriage. Majority, the couples who decided to do the intermarriage must have an open mindset to culture that was brought by their couple including value and norm. If both of them did not have the open mindset, it wouldhappen the imposition of the will to practice a trust, and also value and norm were followed by the couple, so the imperishable of the marriage might not be reached. Each couple tries to take the decision in right solution that is a rational decision not in personal emotional.